2020
DOI: 10.1101/2020.11.10.20229245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health spending and vaccination coverage in low-income countries

Abstract: SummaryBackgroundRoutine childhood immunization is a cost-effective way to save lives and protect people from disease. Some low-income countries (LIC) have achieved remarkable success in childhood immunization, despite lower levels of gross national income or health spending compared to other countries. We investigated the impact of financing and health spending on vaccination coverage across LIC and lower-middle income countries (LMIC).MethodsAmong LIC, we identified countries with high-performing vaccination… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This can include general health systems strengthening and improvements in funding for public health, as well as improvements in maternal and child health that may have driven support for immunization services. [18] Patient and Public Involvement…”
Section: Quantitative Data Collectionmentioning
confidence: 99%
“…This can include general health systems strengthening and improvements in funding for public health, as well as improvements in maternal and child health that may have driven support for immunization services. [18] Patient and Public Involvement…”
Section: Quantitative Data Collectionmentioning
confidence: 99%
“…Among the potential route segments presented in the study framework, the study considered the following that reflected health challenges in SSA and were the most investigated: 1) the PHS-immunisation segment, the results of which suggested that PHS is a predictive factor for vaccination coverage (Castillo-Zunino et al, 2021;De Figueiredo et al, 2016), 2) the immunisation-population health outcomes segment, which revealed that immunisation programmes have prevented one million deaths, and that increased health coverage, as measured by immunisation, is related to a decrease in child and adult mortality (Toor et al, 2021), 3) the PHS -malaria segment, the results of which suggested that PHS is making a substantial contribution to reducing malaria cases in the African region (Omoruyi, 2018;Sede & Nosakhare, 2018), 4) the malaria-female education segment, the results of which disclosed malaria's significantly negative effects on education, including female education; with adverse effects of malaria ranging from school absenteeism (Akazili et al, 2007;Baker et al, 2011;King et al, 2015) to attention deficit and cognitive dysfunction in children (Clarke et al, 2008;Nankabirwa et al, 2013;Opoku et al, 2016), 5) the female education -population health outcomes segment, the results of which suggested that female education has a beneficial impact on the health of the population, as assessed by maternal health, neonatal mortality, as well as under-five and infant mortality (Amwonya et al, 2022;Kaffenberger et al, 2018;Wang, 2021;Wu, 2022).…”
mentioning
confidence: 99%